Lightning Protection Design of Offshore Floating Photovoltaic Power Station - Chengsheng ZHOU (南方能源建设)
[Introduction] This paper mainly discusses the principles, methods and measures of lightning protection design of offshore floating photovoltaic power station to meet the safe operation of offshore floating photovoltaic power station in harsh climate conditions. [Method] Through the in-depth analysis of the marine environment, offshore floating photovoltaic power station structure and lightning characteristics, this study proposed a series of effective lightning protection measures. First, the use of metal structure could improve the lightning resistance capacity of the floating photovoltaic power station. Secondly, the installation of lightning rods could absorb and release lightning energy, reduce the impact of lightning on the power station. In addition, the establishment of the ground grid could effectively disperse the ground potential and reduce the risk of lightning strike. The use of insulating materials helped to reduce the direct invasion of lightning on the power station equipment. At the same time, the installation of monitoring equipment could be real-time monitoring of lightning activities, timely response measures. Regular inspection and maintenance was an important part to ensure the stable operation of the lightning protection system. [Result] The principle and implementation method of each lightning protection measure are elaborated, and some technical problems in lightning protection design are proposed. For example, how to ensure the good grounding of the lightning rod, how to choose the appropriate insulation material, etc. These achievements provide an effective reference for the improvement of the lightning protection capacity of the offshore floating photovoltaic power stations. [Conclusion] The results of this study will help to improve the lightning protection capacity of the offshore floating photovoltaic power stations and ensure the safe operation of the power stations. Based on full consideration of the marine environment, the structure of the offshore floating photovoltaic power station and the lightning characteristics, the appropriate lightning protection measures can effectively reduce the risk of lightning strike and ensure the stable operation of the power station. This is of great significance for promoting the development of renewable energy and protecting the environment. Further study can provide more reference and guidance for lightning protection design to cope with the more complex and harsh climate conditions in the future.